Reagent assessment for detection of ammonium ion‐molecule complexes. (31st October 2013) - Gregory, Kerin E.; Ostrinskaya, Alla; Kunz, Roderick R.
Abstract : RATIONALE: Ammonia (NH3 ) is an important chemical target in sensor applications such as trace explosives detection of ammonium nitrate (NH4 NO3 ) and environmental monitoring. Ion‐molecule reagent chemistries show potential to increase sensitivity in detection systems relying on atmospheric pressure ionization (API) of reagent‐ammonium (M + NH4 + ) complexes. Gas‐phase reagent selection assessment is based on mass spectrometric (MS) determination of binding constants relative to competitive ions and critical energies for ion‐molecule complex dissociation. METHODS: Eight ammonium complexation reagents were identified and gas‐phase ion‐molecule interactions were studied using electrospray ionization. Binding constants were determined, in Log( K ), using the competition method for one host molecule with three guests (NH4 +, Na +, and K + ) in single quadrupole MS. Critical energy determination was based on calibration of threshold activation voltage using collision‐induced dissociation (CID) tandem mass spectrometry (MS/MS). RESULTS: This assessment informs selective binding affinity and intrinsic ion‐molecule critical energy for dissociation. Relative NH4 + binding affinity was highest for sucrose and 4‐ tert ‐butylcalix[6]arene, while 4‐ tert ‐butylcalix[6]arene and methyl acetoacetate showed the highest preferential binding of NH4 + versus Na + and K + . The intrinsic critical energy for NH4 + binding was highest for crown ethers, tetraglyme and methyl acetoacetate. CONCLUSIONS: An MS‐based framework was developed to quantitatively assess API ion‐molecule reagent chemistries based on ammonium selectivity versus competing ions, and intrinsic ammonium binding strength and complex survivability for detection. Methyl acetoacetate is an attractive ammonium reagent for vapor‐phase API techniques given its high vapor pressure, preferential selectivity, and high critical energy for dissociation. Copyright © 2013 John Wiley & Sons, Ltd.